1994
DOI: 10.1161/01.res.74.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate tolerance in vivo is not associated with depletion of arterial or venous thiol levels.

Abstract: Results from in vitro experiments suggest that development of nitrate tolerance is due to a depletion of vascular thiol compounds (ie, cysteine and glutathione [GSH]) necessary for the bioconversion of organic nitrates. However, it is unknown whether in vivo tolerance development is associated with changes in thiol levels. This study measures plasma and vessel tissue GSH and cysteine levels in nontolerant rats, nitratetolerant rats, and rats treated with the two characteristically different thiol donors N-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 25 publications
2
29
0
2
Order By: Relevance
“…It has been suggested that thiols potentiate GTN activity through formation of bioactive SNOs and͞or protect against nitrate tolerance that results from depletion of intracellular thiols. However, the formation of SNO and depletion of intracellular thiol have not been confirmed (28), and alternative hypotheses, such as oxygen radical scavenging by thiol (29), have more recently found favor. We found that the purified mtALDH could catalyze 1,2-GDN formation only when DTT or 2-mercaptoethanol (2ME) were present (although these concentrations of thiol had no effect on their own).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that thiols potentiate GTN activity through formation of bioactive SNOs and͞or protect against nitrate tolerance that results from depletion of intracellular thiols. However, the formation of SNO and depletion of intracellular thiol have not been confirmed (28), and alternative hypotheses, such as oxygen radical scavenging by thiol (29), have more recently found favor. We found that the purified mtALDH could catalyze 1,2-GDN formation only when DTT or 2-mercaptoethanol (2ME) were present (although these concentrations of thiol had no effect on their own).…”
Section: Resultsmentioning
confidence: 99%
“…Although NAC has been shown, in some studies, to reverse nitrate tolerance, controversies still remain about its ef®cacy in preventing nitrate tolerance development under different pathological conditions [25,26]. Results from in vivo experiments in normotensive animals demonstrated that the depletion of vascular thiols, previously thought to be one of the mechanisms responsible for the nitrate tolerance, is not involved, but that an alteration in the cellular thiol turnover could be implicated [27]. Apart from the early studies by Needleman et al [28] who ®rst proposed the presence of thiol as a necessary mechanism for NO donor-mediated vasodilation, little is known about the enzymatic or alternative pathways for formation of in vivo S-nitrosothiols, which are the likely intermediate metabolites responsible for the guanylate cyclase activation [29].…”
Section: Discussionmentioning
confidence: 99%
“…In several reports, administration of N-acetylcysteine may reverse nitrovasodilator resistance (38)(39)(40)(41)(42). However, other studies failed to demonstrate benefit of sulfhydryl repletion (44)(45)(46), and when tissue thiol levels have been evaluated directly, no deficiency was observed (47). The clinically beneficial effect of thiol administration may represent a compensation, not a correction, of the underlying defect.…”
Section: Discussionmentioning
confidence: 99%